2005
DOI: 10.1149/1.1888369
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Oxides in Carbon/Molecule/Metal Molecular Junctions with Titanium and Copper Top Contacts

Abstract: Carbon/molecule/metal molecular junctions were fabricated by metal deposition of titanium or copper on monolayers of nitroazobenzene ͑NAB͒, biphenyl, and nitrobiphenyl ͑NBP͒, and multilayers of NAB and NBP covalently bonded to an sp 2 carbon substrate. The electronic behavior of Ti junctions was extremely dependent on residual gas pressure during E-beam deposition, due to the formation of a disordered Ti oxyhydroxide deposit. The junction resistance decreased with decreasing residual gas pressure, and the hyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(84 citation statements)
references
References 34 publications
5
79
0
Order By: Relevance
“…In addition, Ti can oxidize during deposition, resulting in a molecule/TiOx/Ti (TiOx ¼ titanium oxide) structure with different properties from that of a molecule/metal device. [126,127] While TiO 2 has proven to be a useful component of molecular junctions used for memory applications, [10,74,121,128,129] any user of Ti for fabrication should be aware of possible artifacts from the high reactivity of vapor-deposited Ti atoms. Several other metals have been vapor-deposited on molecular mono-and multilayers, including Au, Ag, Al, and Cu, and in many cases the metal penetrates the monolayer to form metallic ''shorts.''…”
Section: Progress With Ensemble Molecular Junctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Ti can oxidize during deposition, resulting in a molecule/TiOx/Ti (TiOx ¼ titanium oxide) structure with different properties from that of a molecule/metal device. [126,127] While TiO 2 has proven to be a useful component of molecular junctions used for memory applications, [10,74,121,128,129] any user of Ti for fabrication should be aware of possible artifacts from the high reactivity of vapor-deposited Ti atoms. Several other metals have been vapor-deposited on molecular mono-and multilayers, including Au, Ag, Al, and Cu, and in many cases the metal penetrates the monolayer to form metallic ''shorts.''…”
Section: Progress With Ensemble Molecular Junctionsmentioning
confidence: 99%
“…[79,169] In addition, theory showed that the high and low conductance states of the rotaxane devices were consistent with the predictions of density functional theory. [170] Although the rotaxane junctions showed great promise as molecular memory devices, the mechanistic picture was convoluted by subsequent reports from other laboratories that demonstrated switching behavior for similar devices containing non-redox-active molecules, [171] and for molecular junctions known to contain titanium oxide [74,121,126] (titanium was used as an adhesion layer in the rotaxane devices, and partial oxidation of the Ti during evaporation is likely at the backpressures typically used in metal deposition). An example of conductance switching in a molecule/TiO 2 junction is shown in Figure 18.…”
Section: Progress With Conductance Switchingmentioning
confidence: 99%
“…A simplified memristor device physics model [1] matched the experimental behavior [2] of nanocrossbar Pt/TiO 2 /Pt devices. Resistive switching in metal oxides has in fact seen more than four decades of scientific research [4][5][6][7][8][9][10][11][12][13][14][15], motivated in large part by that prospect of a fast and high density NVRAM technology [16][17][18][19][20][21][22][23]. The continuous resistance change exhibited by oxide switches also appears to meet analog switch requirements for neuromorphic computing [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Although each method has certain advantages and disadvantages, it is clear that the entire system must be considered in order to delineate the main factors influencing molecular conduction. Whereas many groups employ thiolate-based self-assembled monolayers (SAMs) on metallic substrates as a base system, we have taken an alternative approach using carbon electrodes (6,(14)(15)(16)(17)(18)(19). The foundation of this paradigm is a flat carbon electrode composed of pyrolyzed photoresist films (PPF) with covalently bonded nanoscopic molecular layers deposited using the electrochemical reduction of diazonium reagents.…”
mentioning
confidence: 99%